Improving iron folic acid consumption through interpersonal communication: Findings from the Reduction in Anemia through Normative Innovations (RANI) project. Issue 1 (January 2022) - Ganjoo, Rohini; Rimal, Rajiv N.; Talegawkar, Sameera A.; Sedlander, Erica; Pant, Ichhya; Bingenheimer, Jeffrey B.; Chandarana, Shikha; Aluc, Aika; Jin, Yichen; Yilma, Hagere; Panda, Bikash
Highlights: Iron folic acid consumption can reduce anemia, but compliance remains low. Interventions can promote interpersonal communication for behavior change. Topic-specific and general interpersonal communication modalities appear effective. Interpersonal communication mediated the intervention effect on iron supplement use. Abstract: Objective: More than half of Indian women of reproductive age are anemic. Regular iron folic acid uptake can prevent and treat anemia. This study investigated the effect of interpersonal communication on improving IFA use among women of reproductive age. Methods: The Reduction in Anemia through Normative Innovations (RANI) Project is a cluster randomized trial that collected longitudinal data from control (n = 1896) and intervention (n = 1898) communities in Odisha, India at Time 1 and six months later at Time 2. Structural equation models assessed the effect of the intervention on iron folic acid use via multiple interpersonal communication pathways. Results: Compared to the control arm, iron folic acid use significantly increased in the intervention arm. Both, general health interpersonal communication and anemia-specific interpersonal communication were augmented in the intervention communities. The impact of the intervention on iron folic acid use was mediated through anemia-specific interpersonal communication. Conclusion: The RANI Project increased interpersonal communication among participants, resulting in increased iron folic acid use for anemia reduction. Practice implications: Strategic use of targeted interpersonal communication to promote behavior change appears to be a viable strategy to increase iron folic acid use to reduce anemia.